Material selection of natural fibre composite webbing sling using rule of mixture - Muhammad, Noryani; Roslan, Nur Ain Fatihah; Abd Rahman, Mohd Syahril (Universiti Putra Malaysia Press, 2024)
Natural fibre composites have grown in popularity as environmental concerns and knowledge about using eco-friendly materials versus synthetic materials. Furthermore, due to their low density and high strength, natural fibres are suitable for use as lightweight composite and reinforcing materials. Webbing slings are commonly used in many industries to lift loads and are typically made of synthetic fibres such as nylon and polyester. This study analysed the physical and mechanical properties, such as density, tensile strength, and Young’s modulus of natural fibre composites. Bananas, pineapple, and jute with polymer matrices such as polypropylene (PP) and epoxy (EP) were used as alternative natural fibre composites for webbing sling application. Furthermore, descriptive statistical analysis was done to summarise the secondary data from the previous study of the physical and mechanical properties of natural fibre and polymer matrix. The rule of mixture (ROM) is used to identify the optimum fibre loading for manufacturing the webbing sling. This study’s volume fractions of fibre were 10%, 30%, and 50%. Using the ROM equation, the results revealed that the higher fibre loading of up to 50% could increase the mechanical properties such as tensile strength and Young’s modulus. Based on the results, pineapple/epoxy composite was the best material to manufacture the webbing sling and complied with the requirements of Product Design Specifications of polyester webbing sling compared to banana and jute composites.